PENGARUH STATUS GIZI TERHADAP PRESTASI BELAJAR SISWA MADRASAH IBTIDAIYAH MUHAMMADIYAH SUKAJATI - Istiana Latifah; Kartini Kartini; Anjar Sulistyani (Institut Agma Islam Hamzanwadi NW Lombok TImur, 2023)
Study Group of Southeast Asia Nutrition Survey (SEANUTS) found light and medium malnutrition case case which predominantly occurs in the are of Indonesia. The finding results whowed that 25,2% children experienced lack of nutrition and 29% of them were stunted. The purposes of this research were to find out the influence of nutrition status and the achievement level of grade 4 and 5 students at Madrasah Ibtidaiyah Muhammadiyah Sukajati. The type of this research employed quantitative method with observational analytic through cross sectional approach. The subjects in this research were 54 grade 4 and 5 students of Madrasah Ibtidaiyah Muhammadiyah Sukajati. The data analysis used were univariate and bivariate analysis using Chi Square Statistic Test then continued by Mann-Whitney test. This research showed that out of 54 respondents based on the nutrition status level, obtained 35 students (64,8%) with normal nutrition status, 15 students (27,8%) with more nutrition status, and 4 students (7,4%) with less nutrition status. Based on the learning achievement result found 46 students (85,2%) had the result under KKM (Minimum Completion Criteria) and 8 students (14,8%) obtained the result above KKM. In the result of bivariate analysis between nutrition status with learning achievement level obtained the result Asymp. Sig. (2-tailed) = 0,124 which meant that the probability value was ginner than 0.05. In other words, it could be stated that the nutrition status had not influence on the students’ learning achievement level.